Partnership Model in Improving Civil Farmers Competitiveness in Bondowoso District - Abul Haris Suryo Negoro; Abdul Kholiq Azhari; Anastasia Murdyastuti (Universitas Pendidikan Ganesha, 2019)
Business partnerships between medium-sized entrepreneurs, large and small entrepreneurs, are carried out in the partnership triangle to increase added value and product competitiveness. Partnerships can overcome the problems of capital, management, entrepreneurship, technology, and network marketing. Widespread market share and cassava marketing network, as a manifestation of increasing competitiveness and added value of cassava, as well as the realization of the partnership principle. Although the partnership model is pseudo, the implementation of the partnership principle is active, the business competitiveness of cassava farmers tends to be high. The high competitiveness of products is reflected in the vast and varied market share of cassava, such as tape businessmen, tapioca flour factories, and sellers/traders of cassava and tape and cakes. Therefore the essential partnership is a transformation for the realization of cassava farmers as competitive producers and entrepreneurs who always produce the products/commodities needed by their customers.